Earthquake attenuation models and its responses to earth zone dam in upper northern part of Thailand - Tawatchai Tanchaisawat (2018)
© Int. J. of GEOMATE. The upper northern part of Thailand is mountainous area which classified as moderate risk by earthquake. This study was focused on the earthquake attenuation model of Abrahamson and Silva (2008). Exciting quake source from the Chiang Rai 2014 earthquake was recorded at earth zone dam site study. The accelerometer was installed in the bottom of dam which is 59 m height, 9 m width and 1,950 m length. The attenuation model is the relationship between acceleration, distance, size of earthquake, period of stabilization, characteristics of seismic sources and geological conditions. This research aims to compare the peak ground acceleration (PGA) between the attenuation models and the data measurement at the dam to check the accuracy of the model. And to study the dynamics analysis in the dam by using two selected time history records with different wave characteristics as: short period (EQ1) and long period (EQ2) to analyze the behavior of the pore water pressure, the stress and displacement in the dam. The results of this study revealed that the Peak Ground Acceleration (PGA) from the attenuation model of Abrahamson and Silva equal to 0.017787 g. And the percentage error of calculated PGA when compared to the PGA from measurement was 6.38. The analysis of the dynamics by using seismic waves with different time duration. EQ1 have made the pore water pressure on the dam higher when the effective stress in the dam decrease, which makes the displacement of the dam more than EQ2.